Pengaruh Infrastruktur Transportasi Terhadap Gross Domestic Product (GDP) Per Capita Pada Negara-Negara Anggota ASEAN - Wafa, M.I.; Narendra, A. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2022)
The purpose of this study is to model the relationship between Gross Domestic Product (GDP) and transportation infrastructure in ASEAN member countries. In addition, this study also compares the data predicted by the model with actual data in Indonesia. Transportation infrastructure includes air transportation, sea transportation, and land transportation (railway). The data used is secondary data from the World Bank (World Development Indicator) 1960-2019. The analytical method used in this research is Statistical Descriptive Analysis and Multivariate Regression Analysis. The results of this study resulted in a multivariate regression model Y = 6,478 – 7,871(X2) + 4,875(X4) – 2,390(X5) – 2,27(X7) + 5,569(X8). This model produces a p-value of 2.619E-13 <0.05, which means that this model has a significance of 2.619E-13 and produces an R2 of 0.95 which means the variables X2 Air transport, passengers carried, X4 Quality of port infrastructure, X5 Container port traffic, X7 Rail lines, X8 Railways, passengers carried affect the Gross Domestic Product (GDP) per capita by 95% and the other 5% is influenced by other factors. This regression model in predicting actual data for the case of GDP in Indonesia is 120.84%, meaning that this model cannot be used to predict actual data in the case of GDP in Indonesia.